(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the effect of the provision and amount of Employee Additional Income Allowance (Tambahan Penghasilan Pegawai, TPP) on employee performance, with instrumentality as a mediating variable and compensation justice perception as a moderating variable. The background of this study stems from the importance of TPP policy within the remuneration system of Indonesian civil servants, particularly in the Department of Education of Padang Lawas Utara Regency, which plays a strategic role in improving the quality of public services. A quantitative survey approach was employed in this research. The study population consisted of 138 employees of the Department of Education of Padang Lawas Utara Regency, with 50 respondents selected as the sample using Slovin’s formula. Data were collected through questionnaires and analyzed using path analysis with a standardized composite (PLS-like) approach, complemented by 5,000 bootstrap replications to test indirect (mediating) effects. The findings reveal that both the provision (X1) and the amount of TPP (X2) do not have a direct significant effect on employee performance (Y). However, both variables significantly affect instrumentality (M), which in turn significantly influences performance. Mediation testing confirms that instrumentality fully mediates the relationship between TPP and employee performance (full mediation). The perception of compensation fairness (Z) was not proven to be significant as a moderating variable. An R2 value of 0.614 for M and 0.625 for Y indicates that the model is able to explain the variation in the construct well.